An advancement of treatment of nasopharyngeal signs of gastroesophageal reflux disease in children against the background of vitamin D deficiency - Boiarska, L. M.; Hrebeniuk, L. V.; Ivanova, K. O. (Journal of Education, Health and Sport, 2020)
The work aims at substantiating the prescription of vitamin D3 for treatment and prevention of nasopharyngeal signs of GERD in children through determining the main risk factors of the development of the disease. Materials and methods. Eighty-eight children aged about 4.6 ± 0.14 years were enrolled in the study. The patients were divided into four groups: group 1 consisted of 22 children with nasopharyngeal signs of gastroesophageal reflux disease (GERD); group 2 comprised 22 children with chronic ENT pathology and without GERD; group 3 was formed of 22 children with GERD and without any ENT pathology; group 4 (control group) included 22 children without an ENT or gastrointestinal pathology. No substantial gender differences were observed in each of the groups. GERD was diagnosed on the basis of symptoms and 24-hour pH monitoring; the test for Vitamin D provision was performed; mucosal immunity characteristics were identified and the contamination of the upper airways mucous membranes was studied. The results are statistically processed using Microsoft Office Excel and Statistica 13 software. Results. Children with GERD with nasopharyngeal signs have been proved to have acute respiratory viral infections (ARVI) more frequently than children with GERD and without ENT pathologies (the number of aggravations is 8.5 (8.0;10.0) and 3.0 (2.0;3.0) respectively (р<0.00001)). The contamination of mucus membranes of oropharynx and nose of the children with nasopharyngeal signs of GERD is represented by opportunistic microflora (in 95.5%) with prevailing Haemophilus influenzae. More than two kinds of microorganism have been inoculated in 63.6% of children (р=0.002), which indicates considerable impairment of colonization resistance in palatal tonsils. Moreover, the majority of the prolonged acid refluxes has been registered in children with the presence of Haemophilus influenza (7,5±1,62 against 3,67±1,2, р=0,04). These data confirm that the acid content of the refluxate not only irritates the mucous membrane of the oral cavity but also leads to the impairment of local immunity mechanisms and creates favourable conditions for the colonization and growth of bacteria which results in the development of lesions in the pharyngeal mucous membrane. Children with GERD accompanied with nasopharyngeal signs are characteristic of vitamin D deficiency which is confirmed by lower levels of 25(ОН)D3. This, in its turn, influences the production of antimicrobial peptides (α-defensins 1-3 and cathelicidins LL 37). Group 1 children present with significantly low levels of antimicrobial peptides (α-defensins 1-3 2474.08±180.4 pg/ml and cathelicidins LL 37 18.89±2,84 pg/ml, р˂0.05) against the background of lower 25(OH)D3 (13.05±0.55 ng/ml, р=0.00001). The determined peculiarities substantiated the introduction of vitamin D3 into therapy for GERD. Children of the treatment group were prescribed vitamin D3 in the dosage of 2000 MU per day for a monthly period, and monotherapy with vitamin D3 in the dosage of 1000 MU per day for a year, daily from September to April, including the break between May and September. Before the treatment, the yearly incidence of the acute respiratory viral disease (ARVD) in the treatment group children was 9.0 [8.0;10.0], and in the control group children, it was 8.0 [7.0; 10.0]. After a year since the beginning of the treatment, the incidence of ARVI in the treatment group children was 4,0 [3.0;4.0], which is significantly lower than in the control group children (5.0 [4.0;6.0], р=0.008). During the year, aggravation of chronic tonsillitis was registered only in 45.5% of the control group children (р=0.03), and GERD symptoms were registered only in 18.2 % of the treatment group patients (р=0.03). Obtained results prove the advisability of including vitamin D3 in the therapeutic regimen of gastroesophageal reflux disease, and its nasopharyngeal signs in particular, in preschoolers. Conclusions. It is typical of children with GERD accompanied by nasopharyngeal signs to demonstrate significantly low levels of antimicrobial peptides against the background of even lower 25(OH)D3 (13.05±0.55 ng/ml, р=0.00001). Children with GERD and nasopharyngeal signs tend to have ARVI more frequently than those with GERD but without ENT pathologies (number of aggravations is 8.5 (8.0;10.0) and 3.0 (2.0;3.0) respectively (р<0.00001)). The prescription of vitamin D3 in the complex therapy for GERD with nasopharyngeal signs allows to decrease the incidence of the acute respiratory viral infection (ARVI) over a year (р=0.008) and to gain stable regression of the clinical symptomatology (р=0.03).